2008
DOI: 10.5194/acp-8-7325-2008
|View full text |Cite
|
Sign up to set email alerts
|

Contribution of very short-lived organic substances to stratospheric chlorine and bromine in the tropics – a case study

Abstract: Abstract. The total stratospheric organic chlorine and bromine burden was derived from balloon-borne measurements in the tropics (Teresina, Brazil, 5 • 04 S, 42 • 52 W) in 2005. Whole air samples were collected cryogenically at altitudes between 15 and 34 km. For the first time, we report measurements of a set of 28 chlorinated and brominated substances in the tropical upper troposphere and stratosphere including ten substances with an atmospheric lifetime of less than half a year. The substances were quantifi… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
106
1

Year Published

2010
2010
2019
2019

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 98 publications
(118 citation statements)
references
References 29 publications
11
106
1
Order By: Relevance
“…Wamsley et al (1994) reported CH 2 Br 2 to have an atmospheric lifetime long enough to reach the stratosphere and CHBr 3 (with shorter lifetime) to contribute negligible amounts to stratospheric Br. The results here are also consistent with Laube et al (2008) who, based on observations, deduced CH 2 Br 2 to be the "dominant" very short-lived SG. Their results, along with Schauffler et al (1998), find CH 2 Br 2 to be present up to ∼18.5 km (∼0.15 pptv).…”
Section: Source Gas Injectionsupporting
confidence: 92%
“…Wamsley et al (1994) reported CH 2 Br 2 to have an atmospheric lifetime long enough to reach the stratosphere and CHBr 3 (with shorter lifetime) to contribute negligible amounts to stratospheric Br. The results here are also consistent with Laube et al (2008) who, based on observations, deduced CH 2 Br 2 to be the "dominant" very short-lived SG. Their results, along with Schauffler et al (1998), find CH 2 Br 2 to be present up to ∼18.5 km (∼0.15 pptv).…”
Section: Source Gas Injectionsupporting
confidence: 92%
“…During a former balloon flight in June 2005 in Teresina the VSLS mixing ratios (analysed for an air sample at 15.2 km) were considerably lower than those analysed in 2008 at nearly the same altitude (Laube et al, 2008). The total Br org from VSLS was 1.25 ppt, while especially the CHBr 3 contribution was unexpectedly low, with only 0.05 ppt Br org .…”
Section: Comparison and Discussionmentioning
confidence: 78%
“…5.1 we determined total uncertainties of the analysed mixing ratios. This calculation was done similar to the procedure described by Laube et al (2008). Statistical errors during the measurements and the systematic error of the calibration scale of the primary standard gas are considered.…”
Section: Scale Uncertaintiesmentioning
confidence: 99%
See 1 more Smart Citation
“…After the flight, the collected samples are analyzed on the abundance of a long list of trace gases by means of gas chromatography. In this comparison we consider five balloon flights that were performed by the University of Frankfurt (Germany) (e.g., Laube et al, 2008).…”
Section: Cryosampler Datamentioning
confidence: 99%